Implementasi Manajemen Monitoring dalam Meningkatkan Kinerja Guru PAI di MTs Sunan Gunung Jati Kabuh - Lailatul Rofi'ah; M. Aliyul Wafa; Khoirun Nisa' (Lembaga Yasin AlSys, 2025)
Monitoring management is a systematic process aimed at overseeing, evaluating, and improving performance within an organization, including in educational settings. This study aims to: (1) describe the monitoring management process in supporting the performance improvement of Islamic Education (PAI) teachers at MTs Sunan Gunung Jati Kabuh; (2) identify the factors influencing its effectiveness; and (3) analyze its impact on teacher performance quality. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation. The results show that the monitoring process is implemented systematically through planning, execution, and evaluation stages. Factors supporting effective monitoring include a well-structured work system, teachers’ commitment to self-development, and active support from the head of the madrasah. The implementation of monitoring management has led to increased teacher professionalism and improved instructional quality. These findings affirm that monitoring serves not only as a control mechanism but also as a developmental tool focused on the sustainable enhancement of educational quality.